Cytomegalovirus after kidney transplantation in 2020: moving towards personalized prevention. Issue 5 (6th December 2020) - Hellemans, Rachel; Abramowicz, Daniel
Abstract: Cytomegalovirus (CMV)-related complications after kidney transplantation remain a substantial challenge. Rather than applying one preventive strategy to all at-risk patients, we can now adapt our strategy at the individual patient level. Antiviral prophylaxis or a strict pre-emptive strategy may be optimal for patients at the highest risk for CMV, while patients at lower risk may benefit particularly from pre-emptive monitoring and the administration of therapy only if needed. CMV-specific T-cell assays may be useful for further refining the pre-transplant determination of CMV risk, and for guiding decisions about antiviral therapy need or duration. An immunosuppressive regimen including a mammalian target of rapamycin inhibitor reduces CMV risk and may thus be an attractive option in some patients. New antiviral agents may further expand our therapeutic arsenal in the near future, and the prospects of CMV vaccination and adoptive T-cell therapy appear to be on the horizon.